Differentiated correction of junior school age children's posture at physical culture trainings - N.S. Razumeiko (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose: to show peculiarities of differentiated correction of junior school age children's posture, considering tonic vibration reflex. Material: the research was conducted with participation of 62 junior school age children (7-10 years old boys and girls). All children have no sport training experience. All children were preliminary examined by qualified medical doctors. Tonic vibration reflex of lumbar spine was registered. Children fulfilled test exercises, which characterized power endurance of abdomen muscles, side of torso and back muscles. Results: external signs of posture disorders were absent in frontal plane. In 35 persons (65.8%) we registered one-side increased reflex excitability of nervous centers: from right side of backbone - in 28 children (72%); from the left side in 17 children (28%). Correction of posture with the help of correcting exercises can give steady effect only with simultaneous formation of correct posture habit. For this purpose it is necessary to create muscular-joint sense of separate body parts' position. Conclusions: for determination of functional potentials of in-born muscular corset it is recommended to fulfill special test exercises. For local influence on lumbar spine muscles it is recommended to use exercise of asymmetric character.